Performance of TCP on wireless fading links with memory - Chockalingam, A.; Zorzi, M.; Rao, R.R. (1998 IEEE International Conference on Communications, 1998)
In this paper, the bulk throughput performance of TCP NewReno over wireless fading links having memory is studied. Like TCP Tahoe, the NewReno version of TCP implements a fast retransmit procedure, but it uses a different congestion window adaptation algorithm. In this study, we show that, for the default parameters of the BSD implementation of TCP over a 1.5 Mbps wireless link having a very small bandwidth-delay product, and as long as sufficiently large advertised window sizes are used, the burstiness in packet errors caused by slow multipath fading (experienced by slow moving users) significantly benefits NewReno compared to i.i.d. packet errors (experienced at vehicular user speeds). We further show that, in such slow fading conditions, NewReno performs no better than Tahoe, mainly due to the high degree of correlation in the fading process.